GNS3 for Security Practitioners - Nieto Jiménez, Ana; López-Muñoz, Francisco Javier (My University, 2019)
The objective of this guide is to provide useful information for the deployment of a virtual laboratory using GNS3 with the aim of testing security features. In this guide GNS3 is used together with other tools for training in network security. It is possible to install all these tools in a single virtual machine. In addition, the virtual machine must have nested virtualisation enabled in order to run inside other virtual machines (e.g. Kali Linux).
This guide is only a small part of the security content that can be learned during the "Master's Degree in Computer Engineering" - Cybersecurity Degree. The guide is used by the students as reinforcement during practical classes, but there is much more content that is not found in the guide. Indeed, the student has access to the virtual machine resulting from the steps in the guide (including all the scripts and networks configured for GNS3), so these steps are only used if the student wants to set up their own environment at home. Moreover, vulnerability analyses are very dependent on the living system. The student learns how to use Metasploit and other pentesting tools during the course, although this is not included in deep in the guide. This guide is only a first step towards cybersecurity training.
Keywords: Seguridad informática; Security; Gns3; Pentesting; Vulnerability analysis; Honeypots; Ids